Advances in Graphene Science (IntechOpen, 2023)
Graphene is proving to be the magic material of the 21th century. It is widely accepted that it is the strongest material ever studied and can be an efficient substitute for silicon. Besides, fascinating properties of graphene, such as the highest electrical conductivity among the discovered substances, have dramatically shocked science and technology world. Graphene is a carbon based layer with high atomic density. Its extraordinary characteristics such as extremely high mechanical strength, hardness, and adjustable thermal and electrical conductivity, as well as excellent surface and optical feature through chemical marking, have received great deal of attention by many researchers. This book collects new advances of this interesting nanomaterial.